Multicluster Pcdh diversity is required for mouse olfactory neural circuit assembly - Mountoufaris, George; Chen, Weisheng V.; Hirabayashi, Yusuke; O’Keeffe, Sean; Chevee, Maxime; Nwakeze, Chiamaka L.; Polleux, Franck; Maniatis, Tom (Science (American Association for the Advancement of Science), 2017)
The vertebrate clustered protocadherin (Pcdh) cell surface proteins are encoded by three closely linked gene clusters (Pcdhα, Pcdhβ, and Pcdhγ). Here, we show that all three gene clusters functionally cooperate to provide individual mouse olfactory sensory neurons (OSNs) with the cell surface diversity required for their assembly into distinct glomeruli in the olfactory bulb. Although deletion of individual Pcdh clusters had subtle phenotypic consequences, the loss of all three clusters (tricluster deletion) led to a severe axonal arborization defect and loss of self-avoidance. By contrast, when endogenous Pcdh diversity is overridden by the expression of a single–tricluster gene repertoire (α and β and γ), OSN axons fail to converge to form glomeruli, likely owing to contact-mediated repulsion between axons expressing identical combinations of Pcdh isoforms.